Integrasi Nilai-Nilai Kristen dalam Pemerintahan - Illu, Jonidius; Jumadi, Jumadi; Paparang, Stenly Reinal; Sarumpaet, Sorimuda (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2025)
This article explores the challenges of applying Christian values within governmental leadership and their impact on the quality of democracy and national diversity. The purpose of this study is to formulate relevant Christian values and integrate them into the context of Indonesia’s public administration. Using a normative-theological and qualitative-descriptive approach, the research analyzes theological and biblical literature, conceptual frameworks, governmental practices, and comparative studies. The findings highlight several core values — including love, justice, integrity, humility, service, and moral responsibility — that can form the foundation of a servant leadership model for government. In conclusion, integrating these Christian values into governmental leadership offers a transformative approach, strengthening democratic practices and restoring public trust through service, justice, and integrity as guiding principles for leaders.